Oil uptake and deep-frying performance of virgin coconut oil and palm solid shortening blends - Omar, Muhammad Nor; Mohd Hasali, Nor-Hazwani; Mohamad Roslee, Farhani; Zuberdi, Ahmad Muzammil; Muhd Nor, Nor Dalilah; Muhd Nor, Nor Nazuha; N. M., Nazreen (Academic Information Press, 2012)
The frying performances of virgin coconut oil (VCO) and palm solid shortening (PS) blends were evaluated. The fresh chickens were fried in a blended frying medium using an open fryer for 8 hours per day intermittently at 30 min interval for five consecutive days. Three types of oils were used; i.e. palm shortening without blending (PS), a blend of VCO: PS (10:90), and a blend of VCO: PS (20:80). The frying oils were collected periodically and their fatty acid composition (FAC), free fatty acid (FFA) content, total polar compound (TPC) and total polymer material (TPM) were determined. In addition, the fried chicken was subjected to the analyses of oil absorption and sensory evaluation. The results showed that the frying performance of the VCO:PS (20:80) blend was better than VCO:PS (10:90) blend and PS in terms of TPM and TPC contents. The VCO:PS (20:80) gave TPC and TPM values of 17.4 and 1.40% respectively, the blend of VCO:PS (10:90) gave values of TPC and TPM of 18. 7 and 2.20% respectively, whilst PS with TPC of and TPM of 20.5 and 3.02 % respectively. Meanwhile, the oil uptake patterns showed that the fried chicken in VCO: PS (10:90) blend absorbed less oil compared to chickens fried in PS and VCO:PS (20:80) blend. The oil uptake in chickens fried in VCO:PS (10:90) blend was 1.75%, while in PS and VCO:PS (20:80) blend were 2.82 and 2.57 % respectively. In term of sensory evaluation, the addition of virgin coconut oil (VCO) to palm based solid shortening (PS) showed significant differences (p < 0.05) on crispiness, taste and overall scores on the 1st , 3rd and 5th day of frying. Although there were no significant difference on oiliness on the 1st and 3rd day, there was a significant difference on the 5th day of frying. In conclusion, the addition of a small proportion of VCO in PS would improve the frying performance of oil as well as sensory scores of the fried products.